Potential Role of BNIP3 in Cardiac Remodeling, Myocardial Stiffness and Endoplasmic Reticulum-Mitochondrial Calcium Homeostasis in Diastolic and Systolic Heart Failure - Chaanine, Antoine H. (2013)
BACKGROUND: We have shown that BNIP3 expression is significantly increased in HF. In this study, we tested the effects of BNIP3 manipulation in HF. METHODS AND RESULTS: In a rat model of pressure overload HF, BNIP3 knockdown significantly decreased LV volumes with significant improvement in LV diastolic and systolic function. There were significant decreases in myocardial apoptosis and LV interstitial fibrosis. Ultrastructurally, BNIP3 knockdown attenuated mitochondrial fragmentation and restored mitochondrial morphology and integrity. On the molecular level there were significant decreases in ER stress and mitochondrial apoptotic markers. One of the mechanisms by which BNIP3 mediates mitochondrial dysfunction is via the oligomerization of the VDAC channels causing a shift of calcium from the ER to mitochondrial compartments leading to the decrease in ER calcium content, mitochondrial damage, apoptosis and LV interstitial fibrosis and hence contributes to both systolic and diastolic myocardial dysfunction, respectively. In systolic HF, the downregulation of SERCA2a, along with an increased BNIP3 expression, further worsen myocardial diastolic and systolic function and contribute to the major remodeling seen in systolic HF as compared to diastolic HF with normal SERCA2a expression. CONCLUSIONS: The increase in BNIP3 expression contributes mainly to myocardial diastolic dysfunction through mitochondrial apoptosis, LV interstitial fibrosis and to some extent to myocardial systolic dysfunction due to the shift of calcium from the ER to the mitochondria and to the decrease in ER calcium content. However, SERCA2a downregulation remains a prerequisite for the major LV remodeling seen in systolic HF.